Energy efficiency improvements in heterogeneous network through traffic load balancing and sleep mode mechanisms - Abdulkafi A.A.; Kiong T.S.; Chieng D.; Ting A.; Koh J. (Kluwer Academic Publishers, 2023)
Heterogeneous network (HetNet) is one of the most promising approaches of IMT Advanced, which not only offers higher capacity and data rate, but also network Energy Efficiency (EE). HetNet is an advanced network that promotes complex cooperation between multiple tiers or sizes of base stations, i.e. macro, micro, pico, and femto base stations towards the above benefits. In this paper, a theoretical model for evaluating the EE of HetNet is proposed. Then, a sleep mode mechanism on picocells is proposed to reduce the total energy consumption which subsequently improves the EE. Simulation results show that EE can be increased by balancing the traffic load between different types of base stations. In fact, the improvement very much depends on the percentage of traffic that is offloaded to picocells. At low to medium traffic load conditions, significant improvements in EE can be observed through the proposed sleep mechanism. It is observed that by combining the sleep mode feature of picocells and load balancing between the different types of base stations in HetNet, further EE improvements up to 68 % for low traffic load and up to 33 % for medium traffic load can be achieved. © 2013 Springer Science+Business Media New York.